The group-based social skills training SOSTA-FRA in children and adolescents with high functioning autism spectrum disorder: study protocol of the randomised, multi-centre controlled SOSTA - net trial - Freitag, Christine M.; Cholemkery, Hannah; Elsuni, Leyla; Kroeger, Anne K.; Bender, Stephan; Kunz, Cornelia Ursula; Kieser, Meinhard (Trials, 2013)
Group-based social skills training (SST) has repeatedly been recommended as treatment of choice in high-functioning autism spectrum disorder (HFASD). To date, no sufficiently powered randomised controlled trial has been performed to establish efficacy and safety of SST in children and adolescents with HFASD. In this randomised, multi-centre, controlled trial with 220 children and adolescents with HFASD it is hypothesized, that add-on group-based SST using the 12 weeks manualised SOSTA-FRA program will result in improved social responsiveness (measured by the parent rated social responsiveness scale, SRS) compared to treatment as usual (TAU). It is further expected, that parent and self reported anxiety and depressive symptoms will decline and pro-social behaviour will increase in the treatment group. A neurophysiological study in the Frankfurt HFASD subgroup will be performed pre- and post treatment to assess changes in neural function induced by SST versus TAU.